2020
DOI: 10.1101/2020.03.22.001875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheCoxiella burnetiiQpH1 plasmid is a virulence factor for colonizing bone marrow-derived murine macrophages

Abstract: 23Coxiella burnetii carries a large conserved plasmid or plasmid-like chromosomally 24 integrated sequence of unknown function. Here we report the curing of QpH1 plasmid 25 from C. burnetii Nine Mile phase II, the characterization of QpH1-deficient C. 26 burnetii in in vitro and in vivo infection models, and the characterization of plasmid 27 biology. A shuttle vector pQGK, which is composed of the CBUA0036-0039a region 28 (predicted for QpH1 maintenance), an E. coli plasmid ori, eGFP and kanamycin 29… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 54 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…One interpretation of these results is that integrants that do not maintain xerL chromosomally are rapidly selected against and not recovered. In light of our data, it will be important to distinguish which phenotypes previously associated with directed plasmid-loss (44) reflect virulence-specific defects (associated with loss of specific virulence factors, such as effectors) and which phenotypes result from the loss of dif /XerL machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One interpretation of these results is that integrants that do not maintain xerL chromosomally are rapidly selected against and not recovered. In light of our data, it will be important to distinguish which phenotypes previously associated with directed plasmid-loss (44) reflect virulence-specific defects (associated with loss of specific virulence factors, such as effectors) and which phenotypes result from the loss of dif /XerL machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apparent vertical inheritance of xerL given its restriction within the order Legionellales, the Coxiella burnetii orthologs of xerL (hereafter xerL Cb ) reside not on the circular chromosome, but on a large ubiquitous plasmid that is critical for virulence (42)(43)(44)(45). While Xer/dif systems have established roles in resolving aberrant plasmid dimers, these are the only Xer sequences within the C. burnetii genome.…”
Section: The Coxiella Burnetii Xerl Ortholog Is Encoded On a Virulenc...mentioning
confidence: 99%
“…Based on the known QpH1 ORF content the resulting strain would grow normally in axenic media. Plasmid incompatibility was recently used as a method to cure NMII of the QpH1 plasmid (Luo et al, 2021). Growth analysis of the ΔQpH1 strain found no growth defect in axenic media but the presence of QpH1 was essential for growth in Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using this technique, Colonne et_al (Colonne et al, 2016) created gene deletions of cbuA0015 and cbuA0016 and showed these mutants had a small atypical CCV in infected THP-1 macrophages (Colonne et al, 2016). Recently a new shuttle vector (pQGK) was developed and was used to cure C. burnetii of the QpH1 plasmid (Luo et al, 2021). This QpH1-deficient strain of C. burnetii had a significant growth defect in bone marrow derived macrophages (Luo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation